2009
DOI: 10.1177/0733464808328606
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Social Engagement to Psychological Well-Being of Older Adults in Assisted Living Facilities

Abstract: This research was supported by a grant from John A. Hartford Geriatric Social Work Faculty Scholars program. The author acknowledges and notes appreciation for the cooperation of the facilities and residents who participated in this study. Assistance from doctoral students was invaluable in interviewing residents and managing the data; the students include Laurel Hitchcock, Fei Sun, Bryan Ford, and Hae Jung Shin. Special thanks are also reserved for Drs. Lucinda Roff, David Klemmack, and Sheryl Zimmerman for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
122
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(130 citation statements)
references
References 48 publications
6
122
2
Order By: Relevance
“…41 This aspect of social participation has also been referred to as social engagement. [40][41][42] A typical measure of informal social participation will ask individuals to indicate how many social activities they have participated in, or community groups of which they are members. Other measures include both social connections and informal social participation as a combined measure of social participation.…”
Section: Informal Social Participationmentioning
confidence: 99%
See 2 more Smart Citations
“…41 This aspect of social participation has also been referred to as social engagement. [40][41][42] A typical measure of informal social participation will ask individuals to indicate how many social activities they have participated in, or community groups of which they are members. Other measures include both social connections and informal social participation as a combined measure of social participation.…”
Section: Informal Social Participationmentioning
confidence: 99%
“…49 The majority of these studies were conducted in the US. 40,42,[50][51][52][53][54][55] One study included Taiwanese participants. 56 Only one study reported a longitudinal study design.…”
Section: Informal Social Participation and Health Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, existing research has shown positive health effects from social engagement between residents at LTC and ALF residences, with enjoyment of mealtimes and perceived friendliness of fellow residents and staff being a significant predictor of life satisfaction for ALF residents (Park, 2009). In addition, a cohesive, supportive facility environment is associated with greater facility satisfaction and lower depression scores for residents (Mitchell and Kemp, 2000).…”
Section: Future Directionsmentioning
confidence: 99%
“…that allow the elderly to live independently as long as possible, but without decreasing their quality of life. Most AL initiatives are based on a top-down approach: the state through its public health system or some private health care organization deploy the new technologies in elderly patients' homes, and health professionals are responsible for checking up on the patient [3] [4]. The installation is a complex task performed by qualified engineers that involves installing and configuring hardware for patient monitoring, the set-up of virtual private networks for sending data to hospitals, and the installation of effectors to help the patient perform some tasks...…”
Section: Introductionmentioning
confidence: 99%